2022
DOI: 10.1111/cas.15370
|View full text |Cite
|
Sign up to set email alerts
|

LINC01605 promotes aerobic glycolysis through lactate dehydrogenase A in triple‐negative breast cancer

Abstract: Breast cancer is the most prevalent cancer diagnosed in women and the major malignancy that threatens women health, thus we explored the role of long noncoding RNA LINC01605 in triple‐negative breast cancer (TNBC). We collected tissue samples from TNBC patients and cultured breast cancer cells to detect LINC01605 levels by RT‐PCR. We then constructed LINC01605 knockdown and LINC01605 overexpressed TNBC cell lines, cell proliferation was measured by CCK‐8 and colony formation assays, cell migration and invasion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
2
10
0
Order By: Relevance
“…As described above, LINC01605 was ltered out prudently. As a promising lncRNA, LINC01605 has been studied in breast cancer [10],…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As described above, LINC01605 was ltered out prudently. As a promising lncRNA, LINC01605 has been studied in breast cancer [10],…”
Section: Discussionmentioning
confidence: 99%
“…To date, LINC01605 has been reported to participate in miR-3960/SOX11 [8] and METTL3/SPTBN2 regulation [12] and to play a role in the EMT signaling pathway with MMP9 [9] and the NF-κB pathway [13] or metabolic processes such as aerobic glycolysis [10]. However, whether LINC01605 regulates tumor cells via the mTOR signaling pathway remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…After identifying the prognostic lncRNAs differentially expressed in normal and KIRC tissues, we comprehensively employed the univariate and LASSO COX regression analysis to determine four lncRNAs (LINC01605, AGAP2-AS1, FOXD2-AS1, and LINC02195) and construct the prognostic signature (CRGscore) associated with the OS. LINC01605 has been demonstrated in triple negative breast cancer, nasopharyngeal carcinoma, colorectal cancer, and other cancers to promote tumor proliferation and invasion through multiple pathways ( Hu et al, 2021b ; Wang et al, 2022a ; Zhao et al, 2022 ). AGAP2-AS1 was confirmed to be a prognostic marker of KIRC through the TCGA-KIRC cohort and a self-collected independent cohort ( Gao et al, 2020 ; Nakken et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, LncRNALINC01605 has been found to be upregulated in a variety of cancers and to accelerate tumor proliferation. Wang et al found that LINC01605 promoted proliferation and invasion of TNBC cells in vitro and directly targeted the upregulation of LDHA expression [ 45 ]. In addition, Chu et al used relevant breast cancer data to search for lncRNAs that negatively regulate PGK1, and experimentally confirmed that LncRNALINC00926 downregulates breast cancer cell proliferation and metastasis by enhancing E3 ligase STUB1-mediated ubiquitination of PGK1 and downregulating the level of glycolytic reprogramming in cancer cells.…”
Section: Lncrnas In Breast Cancer Glucose Metabolismmentioning
confidence: 99%